PERAN GENERASI MILENIAL DALAM PARTISIPASI POLITIK DI INDONESIA DALAM BINGKAI BEHAVIORALISME - Sandiasa, Gede Rama Agus; Pramana, Gede Indra; Puspitasari, Ni Wayan Radita Novi (Jurnal Nawala Politika, 2023)
The facts in the data are that in every legislative election, people who do not exercise their right to vote are always there and tend to increase from every legislative election. According to existing data, the number of voters on the List of Potential Voters for the 2018 East Java Pilgub, for example, was recorded as being 17-25 years old, there were 4,927,761 voters With an explanation of the novice voters as many as 1,863,770 people abstain. From these data it can be seen, if there are many first-time voters who are indifferent to politics, it can be seen how many votes are wasted. David Easton revealed about the psychological model, where this model seeks to understand the behavior that suppresses the learning process with variables such as, Stimulant situations that evoke action in the environment. This view is often justified by data showing that relatively few young people join political parties. They also tend to choose to abstain in elections. However, a number of studies show that the previous view that the younger generation is not interested in politics is wrong. The study states that the younger generation is the group that is considered to care the most about various political issues. Keywords: Abstain Voters; Behavioralisme; Millenial;